피세아테놀과 레스베라트롤의 혈당조절 및 TLR4-NF-κB 경로 조절 작용 - 이희재(Hee Jae Lee); 이해정(Hae-Jeung Lee); 양수진(Soo Jin Yang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2017)
Piceatannol (PIC) is a natural hydroxylated analog of resveratrol (RSV), which is a polyphenol known to extend lifespan by stimulating sirtuins. The aim of this study was to investigate the effects of PIC and RSV on the toll-like receptor 4 (TLR4)-nuclear factor kappa B ($NF-κB$) pathway in mouse hepatocytes and an obese/diabetic KK/HlJ mouse model. AML12 mouse hepatocytes in the absence or presence of palmitic acids (PA) were treated with PIC ($50μM$) or RSV ($50μM$). Male KK/HlJ mice at 20 weeks of age were divided into three subgroups as follows: 1) obese and diabetic control (KK), 2) KK_PIC, and 3) KK_RSV. PIC and RSV were administered orally at a dose of 10 mg/kg/d for 4 weeks. Four weeks of PIC and RSV treatment did not affect body weight or food intake in KK mice. Serum fasting blood glucose was significantly reduced in KK_PIC, and 2 h oral glucose tolerance test area under the curve was significantly reduced by PIC and RSV treatment in KK mice. PIC tended to improve homeostasis model assessment of the insulin resistance index (HOMA-IR) and HOMA beta-cells in diabetic KK mice. TLR4 and $NF-κB$ were down-regulated by PIC and RSV treatments in hepatocytes in the absence or presence of PA. Insulin receptor, AMP-activated protein kinase, peroxisome proliferator-activated receptor gamma, nucleotide oligomerization domain-like receptor family pyrin domain-containing 3, interleukin-1, and $NF-κB$ were altered in PIC-treated livers. Collectively, PIC and RSV inhibited the $TLR4-NF-κB$ pathway, and PIC seems to be more effective than RSV in the regulation of analyzed targets, which are involved in insulin signaling and inflammation in vivo. 본 연구에서는 팔미틴산을 처리한 지방간질환 간세포 모델과 비만/당뇨 동물 모델인 KK/HlJ 마우스를 이용하여 피세아테놀과 레스베라트롤 투여가 염증조절에 주는 영향을 알아보고자 하였다. 4주간의 피세아테놀과 레스베라트롤 섭취는 공복혈당과 경구당부하 검사 2시간 후 AUC를 감소시켜 혈당 조절 개선 효과를 보였다. 또한, 팔미틴산을 처리한 지방간질환 간세포 모델에 피세아테놀과 레스베라트롤을 처리한 결과 염증조절 경로인자인 TLR4와 $NF-κB$의 발현을 유의적으로 감소시켰다. 이를 in vivo 비만/당뇨 동물 모델인 KK/HlJ 마우스의 간 조직에서 확인한 결과 피세아테놀 섭취는 NLRP3와 $NF-κB$의 간 조직에서의 발현을 유의적으로 감소시켰고, IL-1 발현을 감소시키는 경향을 보였다. 하지만 동량의 레스베라트롤 섭취는 이와 같은 항염증 효과를 보이지 않았다. 결론적으로 혈당 조절 개선 효과와 항염증 효과에 있어 피세아테놀이 레스베라트롤보다 우수한 효과를 가지고, 피세아테놀의 항염증 효과는 혈당 조절 개선 효과에 부분적으로 기여할 것으로 제안한다.